Strengthening Anti-Sexual Violence Awareness through Public Dialogue with the Young Generation of Lombok - Sumiadi, Raden; Ahmad, Ahmad; Pranata, Andi; Yasa, I Putu Buda; Rosdiyanti, Evi; Putri, Suci Ramadhani (Abdi Masyarakat, 2025)
Sexual violence is a systemic problem rooted in patriarchal structures and gender bias in society, including in Lombok. Emerging cases, such as those involving religious education figures, show the need for a preventive approach based on collective awareness. This service activity aims to strengthen anti-sexual violence awareness among the younger generation through participatory public dialogue. Taking place at Kedai It's Milk in Mataram City, this activity involved youth, students, law enforcement officials, child protection agencies, and academics. The fishbowl discussion method was used to encourage equal and open participation. As a result, the dialogue raised critical awareness, formed a community action network, and initiated a digital platform as a safe space for sharing and education. This activity confirms the importance of an inclusive dialogical space to dismantle the culture of silence, and encourage social change through multi-stakeholder collaboration and intersectional approaches that are relevant to local conditions.